Characterization of blood pressure and endothelial function in TRPV4‐deficient mice with l‐NAME‐ and angiotensin II‐induced hypertension. Issue 1 (13th January 2014) - Nishijima, Yoshinori; Zheng, Xiaodong; Lund, Hayley; Suzuki, Makoto; Mattson, David L.; Zhang, David X.
Abstract Transient receptor potential vanilloid type 4 (TRPV4) is an endothelial Ca2+ entry channel contributing to endothelium‐mediated dilation in conduit and resistance arteries. We investigated the role of TRPV4 in the regulation of blood pressure and endothelial function under hypertensive conditions. TRPV4‐deficient (TRPV4−/−) and wild‐type (WT) control mice were given l‐NAME (0.5 g/L) in drinking water for 7 days or subcutaneously infused with angiotensin (Ang) II (600 ng/kg per minute) for 14 days, and blood pressure measured by radiotelemetry. TRPV4−/− mice had a lower baseline mean arterial pressure (MAP) (12‐h daytime MAP, 94 ± 2 vs. 99 ± 2 mmHg in WT controls). l‐NAME treatment induced a slightly greater increase in MAP in TRPV4−/− mice (day 7, 13 ± 4%) compared to WT controls (6 ± 2%), but Ang II‐induced increases in MAP were similar in TRPV4−/− and WT mice (day 14, 53 ± 6% and 37 ± 11%, respectively, P < 0.05). Chronic infusion of WT mice with Ang II reduced both acetylcholine (ACh)‐induced dilation (dilation to 10−5 mol/L ACh, 71 ± 5% vs. 92 ± 2% of controls) and the TRPV4 agonist GSK1016790A‐induced dilation of small mesenteric arteries (10−8 mol/L GSK1016790A, 14 ± 5% vs. 77 ± 7% of controls). However, Ang II treatment did not affect ACh dilation in TRPV4−/− mice. Mechanistically, Ang II did not significantly alter either TRPV4 total protein expression in mesenteric arteries or TRPV4 agonist‐induced Ca2+ response in mesenteric endothelial cells in situ. These results suggest that TRPV4 channels play a minor role in blood pressure regulation in l‐NAME‐ but not Ang II‐induced hypertension, but may be importantly involved in Ang II‐induced endothelial dysfunction.